PENGARUH PENAMBAHAN SUSU WHEY BUBUK TERHADAP TOTAL PADATAN TERLARUT DAN KARAKTERISTIK YOGHURT YANG DIHASILKAN - Dida Riyada (Ma'soem University, 2021)
Yoghurt is a product of milk diversification that utilizes milk preservation technology by means of fermentation. Yogurt is a fermented beverage with the addition of Streptococcus thermophillus and Lactobacillus bulgaricus inoculum.The purpose of the study was to determine the effect of increasing the concentration of milk whey powder on the characteristics of yogurt, while the aim was to determine the right concentration of milk whey powder to produce yogurt with good characteristics. The research will be carried out from January to Maret 2021 in Laboratory Food Technology at the Faculty of Agriculture Ma’soem University. The design used in this experiment was a Randomized Block Design consisting of 6 (six) treatments and carried out 4 (four) replications. Treatment A: Addition of Concentration of Milk Whey Powder 5.75%, Treatment B: Addition of Concentration of Milk Whey Powder 6.00% , Treatment Addition of Concentration of Milk Whey Powder 6.25%, Treatment D: Addition of Concentration of Milk Whey Powder 6.50%, Treatment E: Addition of Concentration of Milk Whey Powder 6.75 % , Treatment F: Addition of Concentration of Milk Whey Powder 7.00%.Observations of experimental results have included chemical analysis of total dissolved solids, microbiological analysis of coliforms, and organoleptic analysis of the level of preference for texture, aroma and taste of the resulting yogurt. The results showed that the addition of milk whey powder concentration of 6.50% (D) resulted in a good total dissolved solids of 14.50%. In organoleptic testing of 25 panelists, the level of preference for texture: 3.9 , aroma: 4.45 and taste: 4.73 to the characteristics of the resulting Yoghurt. The results of microbiological testing expressed in Coliform <10. The yogurt from this experiment has also met the quality requirements of SNI 01-2891-1992.